(untitled) (Journal for Studies in Humanities and Social Sciences, 2016)
Gender-based violence in Namibia is pervasive and solutions to it remain elusive. How we address the problem depends on how we frame it. Gender-based is directly linked to unequal relationships of power and do not stand in isolation of structural and cultural violence in our society. There is a long history of gender inequality and gender-based violence that is deeply imbedded in Namibia’s history. Colonialism was violent and its effects still structures representations of masculinity. It has shaped violent hegemonic and subaltern masculinities. There is also a history of gender-based violence embedded in traditional African patriarchy that is often denied. Gender-based violence should not be sought in the biological or psychological essences of individual perpetrators but, instead, in the nature of our society, our histories and ethnographies of violence. This article locates gender-based violence in a social-historical context and seeks to illuminate some of the intersections between violent masculinities, gender, race and class.